MANAJEMEN PROGRAM EKSTRAKURIKULER DALAM PENGUATAN PROFIL PELAJAR ISLAMI SMKIT KHOIRU UMMAH - Lembayu Sutra; Irwan Fathurrocham; Abdul Sahib (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
LEMBAYU SUTRA, Student ID 24861022, Management of Extracurricular Programs in Strengthening the Islamic Student Profile at SMKIT Khoiru Ummah. Master's Thesis. Curup: Graduate Program, State Islamic Institute (IAIN) Curup, Master's Program in Islamic Education Management, 2026. Extracurricular programs play a strategic role in shaping students' character; however, their effectiveness depends on systematic management integrated with Islamic values. Therefore, this study aimed to analyze the management of extracurricular programs in strengthening the Islamic Student Profile at SMKIT Khoiru Ummah. The study focused on planning, organizing, implementation, supervision, and the contribution of extracurricular program management to strengthening the Islamic Student Profile. This research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving the principal, vice principal for student affairs, extracurricular supervisors, teachers, and students. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings revealed that the management of extracurricular programs had been implemented systematically based management functions: planning, organizing, actuating, and controlling. Planning was conducted through annual work meetings and students' needs assessments. Organizing was carried out through a clear division of duties and responsibilities. The implementation of extracurricular activities followed the established schedule and integrated Islamic values into various activities. Supervision was conducted regularly through monitoring and evaluation as the basis for continuous program improvement. The management of extracurricular programs contributed significantly to strengthening the Islamic Student Profile, as reflected in the improvement of students' discipline, responsibility, religiosity, leadership, independence, and social awareness. This study concludes that systematic and sustainable management of extracurricular programs plays an essential role in strengthening the Islamic Student Profile. Keywords: extracurricular program management, Islamic Student Profile, Islamic educational management.